Flame-retardant coating : a means to achieve mechanically stable char - Sim, Yuan Siang (2019)
Steel is the most used material in the infrastructure industry today with a wide range of advantages that allows it to serve its purpose in applications such as buildings. However, in the presence of fire where tempertures could reach 500°C and above, these properties will be altered for the worse. Therefore, it is important for steel structures to be protected and are able to last for a certain period of time for safety concerns. Intumescent coatings allows the steel to retain its aesthetic appearance and offers a protective barrier during a fire by forming a layer of fire-resistant char. Yet, this organic char layer formed usually lack adequate mechanical properties and thus might not effectively protect the underlying steel. To account for this, ceramification was introduced to improve on the mechanical properties where fluxing agents and inorganic fillers are added in conjunction with intumescent systems. This study focuses on the addition of zinc borate (ZB) and boric acid (BA) as fluxing agents with magnesium hydroxide (MDH) as the reinforcing agent into ammonium polyphosphate (APP) and an acrylic resin binder system. The interactions were analysed with thermogravimetric analysis (TGA) and x-ray diffraction (XRD) to investigate the correlation of the products formed with the mechanical behaviour and fire-resistive timings that are observed. It was demonstrated that when ZB and BA were added in equal portions with APP in separate systems, these formluations had 15 – 40% longer fire-resistive timings compared to lesser APP amounts in the furnace test set to simulate fire curve of ISO834 standards. In addition, it was revealed that all compositions had better adhesive and mechanical char properties as compared to traditional organic intumescent coating. Analysis of the residue from the fire tests suggested a possible mechanism where the lower temperature and earlier formation of the stable compound of boron oxide, B2O3, is achieved in BA than ZB thus resulting in better fire-retardant properties.